Potensi Pemanfaatan Limbah Kulit Ari Kopi (Coffee Husk) dalam perikanan (Review) - Diamahesa, Wastu Ayu; Muahiddah, Nuri (Journal of Fish Nutrition, 2023)
The global demand for coffee is increasing each year, and as a result, the number of debris that will be generated will also be as large as coffee husks. Therefore, efforts must be made to employ coffee husks. In the disciplines of biogas, fertilizers, bioethanol, biofuels, enzymes, and bioactive compounds, efforts have been made to utilize coffee husks. However, only two researchers have investigated the use of coffee husks as an alternative raw material and preservative for tilapia flesh in the fisheries industry. This article explains the prospective use of coffee husks in the fisheries sector, particularly in fish farming and processing.